Cathodic vacuum arc multilayer coatings (TiZrSiY)N/NbN : structure and properties depending on the deposition interval of alternate layers - Beresnev, V. M.; Lytovchenko, S. V.; Azarenkov, M. O.; Maksakova, O. V.; Horokh, D. V.; Mazilin, B. O.; Kaynts, D.; Doshchechkina, I. V.; Gluhov, О. V. (My University, 2023)
Two series of multilayer coatings with different numbers of bilayers (268 and 536, respectively) were synthesised using the cathodic vacuum-arc deposition (CVAD) with the simultaneous sputtering of two different cathodes. The first cathode was made of the multicomponent TiZrSiY material, and the second one was made of technical niobium. The coatings were condensed in a nitrogen atmosphere at a constant negative bias potential applied to the substrate. The resulting coatings have a distinct periodic structure composed of individual layers of (TiZrSiY)N and NbN with the thicknesses determined by the deposition interval (10 or 20 s, respectively). The total thicknesses of the coatings determined by the number of bilayers were 11 and 9 microns, respectively. The formation of polycrystalline TiN and NbN phases with grain size comparable to the size of the layers has been identified for both series of coatings. The layers exhibit a columnar structure growth with a predominant orientation (111). The hardness of the experimental coatings depends on the thickness of the layers and reaches 39.7 GPa for the coating with the smallest layer thickness. The friction coefficient of the obtained coatings varies from 0.512 to 0.498 and also depends on the thickness of the layers. A relatively large value of the friction coefficient is due to high roughness and the presence of a droplet fraction on the surface as well as in the volume of the coatings.
Keywords: Cathodic vacuum-arc deposition; Multilayer coatings; Layer number; Texture; Microhardness; Tribological properties; Friction parameters